Lokarāja meṃ praśāsana kā ādarśa : Pradhāna Mantrī Śrī Morārajī Desāī ke vicāra - Desai, Morarji, 1896-1995 (Vijñāpana aura Drśya Pracāra Nideśālaya, Sūcanā aura Prasāraṇa Mantrālaya, Bhārata Sarakāra, 1978)
On desirable administration in democracy; portions from lectures given by the Indian Prime Minister.